Design Of Low Voltage Main Switchboard 415240V For Electrical Power Distribution System In Commercial Building - Abdul Rahim, Saiful Azhar (Universiti Sains Malaysia, 2006)
This project emphasizes the design of Low Voltage Main Switchboard (415/240V) in commercial building with the purpose to distribute electrical power to the load together with protection system. The main objective of this project is to design a Low Voltage Main Switchboard consists of Emergency Standby Supply (Generator set and Uninterruptible Power Supply), Fire Protection System and Satellite Master Antenna Television (SMATV). Besides that, this project give a clear understanding about electrical equipment such as circuit breaker, busbar system used in Main Switchboard, protection relays such as overcurrent and earth leakage protection and many others equipment. The project design starts with load data calculation where maximum demand P = 520 kW, total current I = 850 A and voltage supply V = 415 V (Low Voltage). With this information we get from the load data calculation, the result is we can size up the main cable, main circuit breaker, metering and measuring instrument, and others equipment include in Main Switchboard. For future work, more research could be done in this project in order to design a high efficient system in electrical power distribution.